PENILAIAN ARSIP MAKRO DI FAKULTAS ILMU TARBIYAH DAN KEGURUAN (FITK) UIN SYARIF HIDAYATULLAH JAKARTA: Array - Lolytasari Lolytasari (Arsip Nasional Republik Indonesia, 2013)
This research analyzed records macro-appraisal at the Faculty of Tarbiyah and Teaching Sciences (FITK) UIN Syarif Hidayatullah Jakarta. The analyzing aspects are the activity of records macroappraisal at the FITK UIN Syarif Hidayatullah Jakarta and identification of assessment criteria of records macro-appraisal based on anorganizational structure. This is a qualitative research of macroappraisal through a business function observation. Collecting data were conducted by means of observations, questionnaires and interviews. The result showed that records macro-appraisal conducted partially in every work unit. It occurred since there was no guideline of records macroappraisal. The implementation of records macro-appraisal as the standard of records assessment and basis of records Schedule were based on experiences and expertise of an archives manager. Records appraisal did not refer to ANRI guidelines. The recommendation given for the FIKTUIN Jakarta is to continue the research on records macro-appraisal as a preliminary step in organizing records macro-appraisal and records creation guidance of the center embryo of a records storage